Post-theory : new directions in criticism - McQuillan, Martin (Edinburgh University Press, 1999)
Post-Theory brings together some of the most prominent figures and rising stars in the field of critical theory. Contributers include, Catherine Besley, Patricia Duncker and Nicholas Royle.